Recurrent criminal behavior and executive dysfunction - Santos Barbosa, Manuel Fernando; Coelho Monteiro, Luis Manuel (The Spanish Journal of Psychology, 2008)
Objective: To experimentally test the hypothesis that people who repeatedly participate in forms of non-violent crime exhibit an executive deficit detected in tests of high ecological validity, having changes in prefrontal functioning as neurophysiologic basis. Participants and Methods: A battery to assess executive dysfunction was administered – the Behavioural Assessment of the Dysexecutive Syndrome (BADS) –to an experimental group of 30 inmates convicted of crimes against property (mean age = 39.3, SD =9.98), and a control group of 30 (mean age = 32.7, SD = 11.8), all male. Results: The group of recurrent inmates performed significantly worse than the control group in their global scores on the battery, as well as in the majority of subscales. Conclusion: Without removing from consideration the fact that sample size was not very large and, primarily, alerting ourselves to the dangerous hypothesis of a “frontal criminogenesis,” the authors interpret criminal recurrence and resistance to penal measures in terms of the scarcity of control that individuals from the experimental group have over their behavior and its respective consequences.